Performance Optimization and Comparison of CNT Interconnect with Copper at VDSM Technology (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
As the CMOS process technology continues to scale, standard copper (Cu) interconnect will become a major hurdle for the best performance at very deep submicron (VDSM) technology node. The carbon nanotube (CNT) bundles have potential to provide an attractive solution for the higher resistivity and electromigration problems faced by traditional copper interconnects in VDSM technology node. This paper presents important guidelines to minimize the resistance, capacitance and inductance of a mixed CNT bundle interconnect for achieving best performance. The performance of mixed CNT bundle and copper is then compared at local and global interconnects level at 22nm technology node. HSPICE simulations carried out using Berkeley predictive technology model (BPTM) at an operating frequency of 1GHz, shows that for interconnect length of 1000um, the mixed CNT and optimized CNT (CNT_Opt) bundles are 1.98X and 2.20X faster, 74% and 84% more energy efficient respectively than the Copper interconnects.